POPULAR KNOWLEDGE AND CONCEPTIONS IN SCHOOL - Küster, Joziani; Ribeiro, Marcus Eduardo Maciel; Robaina, José Vicente Lima (Cadernos de Educação Tecnologia e Sociedade, 2019)
This article aims to bring conceptions of knowledge that have passed through generations, which is called popular knowledge or primeval knowledge (CHASSOT, 2016) and which are spread in specific communities by ancestors. This article presents conceptions about school learning based on popular knowledge. This is an extract from the master thesis project that one of the authors develops. The investigation consists in a case study in where data will be collected through questionnaires and interviews during the project. Then, these data will be treated through Discursive Textual Analysis (MORAES; GALIAZZI, 2011) aiming to produce metatextes that allow the comprehension of the way that popular knowledge in those regions is consolidated in the form of school activities. It aims to identify teachers' opinions on the importance of this work based on popular knowledge; recognize the influence of popular knowledge on the science learning concepts of the schools in Rio do Oeste, Santa Catarina; and understand how the scientific knowledge at schools interferes with popular knowledge.